2015
DOI: 10.1039/c5ce00909j
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in polyoxoniobates decorated and stabilized via transition metal cations or clusters

Abstract: 5Transition-metal (TM) cations and clusters have been widely used to functionalize polyoxometalates (POMs) of the tungsten, molybdenum and vanadium, as their acidic nature, which made them compatible with addendum TM cations. Together with the well understanding of their solution behavior, a great achievement of TM-based POMs has been made, which exhibited potential applications in many fields. Comparably, fewer polyoxoniobates (PONs) were obtained as the poor understanding of their solution 10 behavior, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 112 publications
0
26
0
Order By: Relevance
“…, SbO 3 3À , IO 6 5À etc.) (Cameron et al, 2014;Chen et al, 2013); (ii) they can exist over a wide pH range, which is suitable for the existence of transition metal (TM) cations, rare earth (RE) cations or other clusters (Wu et al, 2015); (iii) the stereochemical effect of the lone electron pairs orientated on trigonal pyramidal XO 3 groups (X = As III , Sb III , Bi III , Se IV and Te IV ) encapsulated at the centres of POMs can to some degree hinder the closure of cage-like POM intermediates forming lacunary hetero-POT building blocks, which favours the self-assembly of large poly(hetero-POT)s (Zhao, Li, Ma et al, 2016); (iv) these lacunary hetero-POT precursors can usually work as excellent multidentate inorganic ligands to coordinate with TM/RE electrophiles generating TM-substituted hetero-POTs, REsubstituted hetero-POTs or even TM-RE heterometalsubstituted hetero-POTs (Du et al, 2013;Rodriguez-Albelo et al, 2009). Up to now, abundant functional hetero-POTs were isolated by introduction of TM or RE centres into the defect sites, which almost complete its full coverage of POM chem-istry, from purely synthetic strategies aimed at explaining the mechanism of the assembly processes, to the practical research fields that attempt to expand the scope of applications of POMs (Liu et al, 2016).…”
Section: àmentioning
confidence: 99%
“…, SbO 3 3À , IO 6 5À etc.) (Cameron et al, 2014;Chen et al, 2013); (ii) they can exist over a wide pH range, which is suitable for the existence of transition metal (TM) cations, rare earth (RE) cations or other clusters (Wu et al, 2015); (iii) the stereochemical effect of the lone electron pairs orientated on trigonal pyramidal XO 3 groups (X = As III , Sb III , Bi III , Se IV and Te IV ) encapsulated at the centres of POMs can to some degree hinder the closure of cage-like POM intermediates forming lacunary hetero-POT building blocks, which favours the self-assembly of large poly(hetero-POT)s (Zhao, Li, Ma et al, 2016); (iv) these lacunary hetero-POT precursors can usually work as excellent multidentate inorganic ligands to coordinate with TM/RE electrophiles generating TM-substituted hetero-POTs, REsubstituted hetero-POTs or even TM-RE heterometalsubstituted hetero-POTs (Du et al, 2013;Rodriguez-Albelo et al, 2009). Up to now, abundant functional hetero-POTs were isolated by introduction of TM or RE centres into the defect sites, which almost complete its full coverage of POM chem-istry, from purely synthetic strategies aimed at explaining the mechanism of the assembly processes, to the practical research fields that attempt to expand the scope of applications of POMs (Liu et al, 2016).…”
Section: àmentioning
confidence: 99%
“…[3][4][5][6] This family has accelerated dramatically over the last 15 years, and a vast expansion of available PONbs has been reported. [7][8][9][10][11][12][13][14] In this context, the class of Nb/W addendum heteropolyoxometalates develops slowly since the pioneering work reported by Finke and Droege in 1984. 15 Recently, some other Nb/W addendum heteropolyoxometalate clusters have been communicated.…”
Section: Introductionmentioning
confidence: 99%
“…35 The successful synthesis of these compounds has been thoroughly demonstrated that the NbO 2 groups are actually more basic and reactive than their oxotungsten counterparts. Therefore, {SiW 9 The solution was adjusted to pH 2.3 and heated to 90 C for 5 h, followed by the addition of CsCl (Scheme 1a). Interestingly, polyanion 1a can be only crystallized with the need for Cs + cation (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…discovered the first Keggin-type heteropolyoxoniobate anion [SiNb 12 O 40 ] 16−   6 , and thereafter, PONb species has become one of the most widely investigated families of molecules in the POM family 727 . However, the researches of PONb clusters are mainly focused on alkaline system owing to the basic nature of the hexaniobate Lindqvist ion [Nb 6 O 19 ] 8− ( Nb 6 ) 7, 12 , the most common used starting material in PONb chemistry. In this context, the amphoteric or complexed transition-metal (TM) can be introduced to obtain novel heterometallic PONbs 12, 2227 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the researches of PONb clusters are mainly focused on alkaline system owing to the basic nature of the hexaniobate Lindqvist ion [Nb 6 O 19 ] 8− ( Nb 6 ) 7, 12 , the most common used starting material in PONb chemistry. In this context, the amphoteric or complexed transition-metal (TM) can be introduced to obtain novel heterometallic PONbs 12, 2227 . Nevertheless, most of the reported TM-containing PONb derivatives are synthesized by hydrothermal or hydrothermal-diffusion methods.…”
Section: Introductionmentioning
confidence: 99%